Lampung Macroeconomy: A Model of Social Accounting Matrix - Fitriani Fitriani; Sutarni Sutarni; Evi Yuniarti; Hanung Ismono; Dyah Aring Hapiana Lestari; Dwi Haryono (Muhammadiyah University Press, 2021)
Indonesia’s economics contribute dominantly to the agriculture sector. Its also represented in Lampung Province, Indonesia. The main goal of the research was to design an agricultural development model. The method is approached by Social Accounting Matrix (SAM) model. SAM Lampung was designed as a macro model with an 8 x 8 matrix. Secondary data of Input-Output Lampung 2010 as basic data. Data sources get from Lampung Statistic Board and agriculture agency, industrial and trade agency, and Indonesia monetary authorization. The result revealed that based on the total multiplier, the agriculture sector is still dominant in Lampung’s economic structure. Unfortunately, agriculture’s household multiplier was the lowest compared with trade and industry, and services. This fact indicates that agriculture development is not adequate yet enhancing the farmer’s income. Agriculture development needs to address farmer’s households. Stimulation on agriculture exogenous balance is necessary to enhance farmers’ household income.